Engineering economy - Blank, Leland T. (McGraw-Hill, 2005)
Engineering Economy, 6th edition, provides undergraduate students and practicing professionals with a solid preparation in the financial understanding of engineering problems and projects, as well as the techniques needed for evaluating and making sound economic decisions. Information on cost estimation, depreciation, and taxes has been updated to conform to new tax laws and a majority of the end-of-chapter problems are revised or new to this edition.